Empowering Young Researchers: The Influence of Research Consultations on the Perceived Preparedness of Grade 11 Students in Research Writing - Aure, Abigail D.; Ibañes, Shaina B.; Ty, Gerald Jad P.; Bagares, Rob Cris A. (Future Science / FSH-PH Publications, 2024)
s the Philippines strives best to teach Filipino learners how to become globally competent learners and workers of the world in the future through its implementation of K-12 and the teaching of research subjects, it is befitting to assess how students are being prepared for writing research. While other countries conduct research consultations by scheduling appointments with librarians, the schools in the country make the most out of their teachers by serving as research consultants at the same time. This study analyzes how research consultations with Practical Research 1 teachers influence the perceived preparedness of 16 Grade 11 students in one non-sectarian school in Marikina City through qualitative narrative research. Based on the findings, it is concluded that the students view research consultations as a beneficial activity that improves their research writing and communication skills. Although beneficial, challenges such as incoherent feedback from validators, appointment conflicts, and miscommunication hinder them from maximizing the use of research consultations. In the end, the researchers recommend improving research consultation tools and management, and conducting a longitudinal quantitative approach to assess the effectiveness of research consultations in enhancing the competencies of students in research writing.